Badis laspiophilus, a new miniature addition to the ichthyofauna of West Bengal, north-eastern India, with observations on its ecology and preliminary notes on its ethology (Actinopterygii: Perciformes: Badidae) - Valdesalici, Stefano; Voort, Stefan Van Der (Zootaxa, 2015)
Badis laspiophilus is described from the Torsa River drainage, West Bengal, India. It can be distinguished from congeners by a combination of characters which include a small size (15.7–21.0 mm SL), 14–16 circumpeduncular row scales, interorbital width 6.7–8.9 % SL, upper and lower jaws 8.2–9.2 and 10.2–13.4 % SL, respectively, presence of two dorsal-fin blotches and a single round blotch on the anal fin, and absence of cleithral, opercle and dorsolateral caudal peduncle blotches. Its benthic ecology is discussed and the Badis singenensis species group is diagnosed, of which B. laspiophilus and B. singenensis are considered members.